CARBON CAPTURE AND STORAGE REGULATION UNDER INDONESIAN ADMINISTRATIVE LAWJURIDICAL ANALYSIS OF PRESIDENTIAL REGULATION NO. 14 OF 2024 AND ITS IMPLEMENTATION - Audrey Kartika Putri; Indah Dwi Qurbani; Mardian Wibowo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the legal framework of Carbon Capture and Storage (CCS) in Indonesia, focusing on the enactment and implementation of Presidential Regulation No. 14 of 2024 concerning the Organization of Carbon Capture and Storage Activities. The objective of this research is to assess how the regulation provides legal certainty, administrative accountability, and clarity of state control in CCS governance as a strategic instrument to achieve Indonesia’s Net Zero Emission (NZE) target by 2060. The study employs a normative juridical approach, relying on primary legal materials including laws, presidential regulations, and ministerial decrees, as well as secondary sources such as academic literature, legal doctrines, and previous studies. Data collection was conducted through library research and analyzed using grammatical and systematic interpretation to examine the relationship between CCS regulations within the broader Indonesian legal system. The results indicate that the regulation establishes an initial legal basis for CCS governance, particularly in terms of site characterization, licensing, monitoring, and post-operational responsibilities. However, challenges remain, including overlapping institutional mandates, the absence of comprehensive technical guidelines for Monitoring, Measurement, and Verification (MMV), and legal uncertainties for enterprises participating in CCS projects. These findings highlight the necessity of harmonizing CCS regulations with existing environmental and energy laws, as well as strengthening administrative law mechanisms to ensure compliance, transparency, and public accountability. In conclusion, Presidential Regulation No. 14 of 2024 represents a progressive step in integrating CCS into Indonesia’s climate policy framework, but its effectiveness will depend on consistent implementation, the formulation of detailed technical rules, and institutional coordination. Reinforcing the principles of administrative law, particularly legal certainty, the rule of law, and state responsibility, is crucial to ensure that CCS not only contributes to emission reduction but also aligns with the principles of good governance.